The Preparation Of Calcia-based Ceramic Slurry For Rapid Manufacturing Hollow Turbine Blade Based On Stereolithography - Yang, Qiang (2016)
A new water-soluble calcia-based integral ceramic mold was developed for hollow turbine blade by combining stereolithography and gel casting. The influences of solid loading, and grain gradation on the rheological property of calcium carbonate ceramic slurry was investigated. For the more, the effect of zirconia additions on the hydration resistance of calcia-based ceramic mold was studied. The results show that the calcium carbonate ceramic slurry with 60 vol % solid loading and 0.83 Pa·s viscosity was obtained by three graded grain gradation with 40μm:5μm:2μm=56:5:39. The drying shrinkage of green body is less than 0.08% by vacuum freeze drying and zirconia can improve the hydration resistance of calcia-based ceramic mold significantly. The slurry of calcium carbonate ceramic can be used for manufacture the integral calcia-based ceramic mold for turbine blade and the calcia-based integral ceramic mold fabricated by this method can overcome the poor leachability of Al2O3 or SiO2 based ceramic molds and decrease the production costs.